Bevacizumab for non‐small‐cell lung cancer: A nested case control study of risk factors for hemoptysis. Issue 12 (12th December 2016) - Goto, Koichi; Endo, Masahiro; Kusumoto, Masahiko; Yamamoto, Nobuyuki; Ohe, Yuichiro; Shimizu, Ayaka; Fukuoka, Masahiro
Abstract : Potentially life‐threatening, serious hemoptysis is an adverse event associated with bevacizumab in non‐squamous non‐small‐cell lung cancer (NSCLC) trials. Suggested risk factors include central tumor location and cavitation; however, the profile of hemoptysis occurrence in clinical practice is still unclear. A nested case‐control study was conducted to assess the onset profile and risk factors for hemoptysis in bevacizumab‐treated patients in a real‐world setting in Japan. After bevacizumab was approved for NSCLC, physicians registered all NSCLC patients scheduled for bevacizumab therapy, from November 2009 to August 2011. Patients developing grade 2 hemoptysis requiring an injectable hemostatic agent or grade ≥3 hemoptysis were selected as case subjects, matched with four control subjects each. Case report forms were collected after an observation period of 24 weeks. Radiologists assessed blinded thoracic images. Risk factors for hemoptysis were assessed by univariate and stepwise multivariate analysis. Of 6774 patients registered, 23 (0.3%) experienced grade ≥2 drug‐related hemoptysis. A total of 104 patients (21 cases, 83 controls) were analyzed by central reviewers for risk factors of hemoptysis occurrence. In the univariate analysis seven factors were associated with hemoptysis. In the step‐wise multivariate analysis, prior thoracic radiotherapy ( P = 0.1844), presence of tumor exposure in the central airway ( P = 0.0256) and concomitant radiotherapy ( P = 0.1169) were identified as risk factors for hemoptysis. While the incidence of hemoptysis was low in the real‐world setting in Japan, the three risk factors identified, prior thoracic radiotherapy, presence of tumor exposure in the central airway and concomitant radiotherapy, should be considered when selecting patients for bevacizumab treatment. Although technically classed as a clinical trial, a nested case‐control study was a non‐interventional surveillance study analyzing all NSCLC patients receiving bevacizumab in Japan, therefore it was not registered as a phase II/III clinical trial would be. Abstract : This manuscript reports the incidence of hemoptysis in 6774 Japanese patients, which was low in this real‐world setting, and the resulting uni‐ and multivariate analysis to identify associated risk factors. Prior thoracic radiotherapy, presence of a tumor mass in the central airway and concomitant radiotherapy, were identified as risk factors for hemoptysis and should be considered before starting bevacizumab treatment, in order to ensure patients are receiving the most appropriate therapy.